Analysis of the Leadership Style of the Head of The Library at the Muhammadiyah University of Jakarta - Nurdiansyah Arifin; Vidiastuti Muljono (Syarif Hidayatullah State Islamic University of Jakarta, INDONESIA, 2022)
The University of Muhammadiyah Jakarta Library is one of the private university libraries which has approximately 20 librarians spread across all faculties. Each faculty consists of up to 1 to 2 librarians. The University of Muhammadiyah Jakarta campus consists of 2 campuses, namely the Cirendeu Campus and the Cempaka Putih Campus. The Central Library is located on the Cirendeu Campus. This study aims to analyze the leadership style applied by the head of the library at the Muhammadiyah University in Jakarta or abbreviated as UMJ. The method used in this study is a qualitative method with data collection techniques, interviews, and observations. The observation was done to analyze matters related to research, namely the leadership style applied by the head of the library. Data analysis includes data reduction, data presentation, and drawing conclusions or verification. This study shows that the application of leadership style in the UMJ library adopts a situational leadership style system by measuring it through four aspects, namely informant style, sales style, participatory style, and delegation style. The ideal leadership element is already owned by the head librarian of the University of Muhammadiyah Jakarta, it can be seen from the positive stigma that his subordinates put out, thus making the library a library development that can happen quickly. Furthermore, judging from the application of the leadership style of the head of the Muhammadiyah Jakarta university library, it is very suitable to be applied in the Muhammadiyah Jakarta University library because it can adapt to the work environment that occurs in that place.